Representation of Cultural Ambivalence in Eliza Hamilton’s Translation of the Letters of A Hindoo Rajah - Paudel, Prakash (Contemporary Research: An Interdisciplinary Academic Journal, 2021)
Eliza Hamilton in her two-volume epistolary novel Translation of The Letters of A Hindoo Rajah (1819), by projecting two characters who undergo the oppositional experiences during their contact with English people, creates an ambivalent situation which neither represents England as totally positive nor India as completely negative. The two perspectives of Zaarmilla and Sheermaal exclude one another’s rendering. To unpack this contradictory narrative position, the concept of acculturation and cultural stress, especially formulated by John W. Berry is taken in interlocution. By rendering these two sorts of antithetical narratives juxtaposed together confirms the dynamics of ambivalence which does not regard Saidaian notion of Orientalism intact.